Self-regulation of motor vehicle advertising: is it working in Australia? - Donovan, Robert; Fielder, Lynda; Ouschan, Robyn; Ewing, M. (Elsevier Science, 2011)
There is growing concern that certain content within motor vehicle advertising may have a negative influence on driving attitudes and behaviours of viewers, particularly young people, and hence a negative impact on road safety. In response, many developed countries have adopted a self-regulatory approach to motor vehicle advertising. However, it appears that many motor vehicle advertisements in Australia and elsewhere are not compliant with self-regulatory codes. Using standard commercial advertising methods, we exposed three motor vehicle ads that had been the subject of complaints to the Australian Advertising Standards Board (ASB) to, N= 463, 14–55 year olds to assess the extent to which their perceptions of the content of the ads communicated themes that were contrary to the Australian self-regulatory code. All three ads were found to communicate messages contrary to the code (such as the vehicle’s speed and acceleration capabilities). However, the ASB had upheld complaints about only one of the ads. Where motor vehicle advertising regulatory frameworks exist to guide motor vehicle advertisers as to what is and what is not acceptable in their advertising, greater efforts are needed to ensure compliance with these codes. One way may be to make it mandatory for advertisers to report consumer pre-testing of their advertising to ensure that undesirable messages are not being communicated to viewers.